Degrees of ritualization: language use in Mongolian shamanic ritual - Dulam, Bumochir (Shaman, 2010)
Based on present shamanic societies, the article identifies types of Mongol shamanic chants and their characteristics and distinctions, where previously these have been understood as a single long chant uttered during shamanic rituals. Next, by developing the characteristics of the types of chants, an explanation is suggested for the opposing Euro-American theories of ritual. The article proposes that ritualization has four inseparable degrees, starting from everyday actions with full propositional and intentional characteristics and then progressively losing propositional force and intentionality through the degrees of ritualization until the highest nonintentional and nonpropositional degree is reached.